Trimerization and cyclization of reactive P-functionalities confined within OCO pincers. Issue 46 (25th August 2021) - Chinen, Beatrice L.; Hyvl, Jakub; Brayton, Daniel F.; Riek, Matthew M.; Yoshida, Wesley Y.; Chapp, Timothy W.; Rheingold, Arnold L.; Cain, Matthew F.
Abstract : Attempted synthesis of OCO-supported 10–P–3 species led to trimerization or cyclization. Abstract : In order to stabilize a 10–P–3 species with C 2v symmetry and two lone pairs on the central phosphorus atom, a specialized ligand is required. Using an NCN pincer, previous efforts to enforce this planarized geometry at P resulted in the formation of a C s -symmetric, 10π-electron benzazaphosphole that existed as a dynamic "bell-clapper" in solution. Here, OCO pincers 1 and 2 were synthesized, operating under the hypothesis that the more electron-withdrawing oxygen donors would better stabilize the 3-center, 4-electron O–P–O bond of the 10–P–3 target and the sp 3 -hybridized benzylic carbon atoms would prevent the formation of aromatic P-heterocycles. However, subjecting 1 to a metalation/phosphination/reduction sequence afforded cyclotriphosphane 3, resulting from trimerization of the P(i ) center unbound by its oxygen donors. Pincer 2 featuring four benzylic CF3 groups was expected to strengthen the O–P–O bond of the target, but after metal–halogen exchange and quenching with PCl3, unexpected cyclization with loss of CH3 Cl was observed to give monochlorinated 5 . Treatment of 5 with ( p -CH3 )C6 H4 MgBr generated crystalline P-( p -Tol) derivative 6, which was characterized by NMR spectroscopy, elemental analysis, and X-ray crystallography. The complex 19 F NMR spectra of 5 and 6 observed experimentally, were reproduced by simulations with MestreNova.